Analisis Strategi Baznas Provinsi Bengkulu Dalam Upaya Mempertahankan Eksistensi UMKM Dengan Pendekatan Maqashid Syariah - Faizah, Nur; Oktarina, Amimah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
The Covid-19 pandemic that has been going on for the last 2 years has become a global issue, including in Indonesia. In the midst of the COVID-19 pandemic, BAZNAS Bengkulu Province played a role in assisting affected MSME actors by providing training, roles in education, social and humanitarian fields. In this paper, we will discuss the strategy of the Bengkulu province baznas in an effort to maintain the existence of MSMEs with a maqashid sharia approach. By using field research methods and qualitative approaches, the data will be obtained and analyzed through qualitative descriptive analysis techniques. Data obtained through in-depth observation, interviews and documentation. The results show that BAZNAS Bengkulu has several strategies to maintain the existence of MSMEs in the midst of the Covid-19 pandemic, including consumptive and productive strategies, such as the rice ATM assistance, the zakat kyai program and the Immune maintenance program and productive economic assistance for the affected pesantren. from Covid-19.